Tumor regression grade predicts recurrence-free survival in intermediate-advanced hepatocellular carcinoma after conversion therapy - Zhang, Haili; Yang, Tongshu; Huang, Luping; Li, Bo; Xu, Hongwei; Wei, Yonggang (Frontiers in Immunology, 2025)
BackgroundConversion therapy provides patients with intermediate-advanced hepatocellular carcinoma (HCC) an opportunity for radical resection, but the prognostic significance of residual tumor in resected specimens remains unclear. This study aimed to evaluate the impact of pathological tumor regression grade (TRG) on postoperative recurrence in HCC patients who underwent conversion therapy.MethodsData from HCC patients who received conversion therapy between September 2018 and September 2022 were retrospectively collected. Patients were categorized based on TRG status: TRG1a, TRG1b, TRG2, and TRG3. Multivariate regression analyses were performed to identify independent predictors of recurrence and factors associated with optimal TRG status after resection.ResultsA total of 117 patients who underwent conversion resection were enrolled. Multivariate regression analysis revealed that achieving TRG1b was not significantly associated with recurrence, whereas TRG2 (HR = 4.25, P = 0.012) and TRG3 (HR = 6.20, P < 0.001) were independently associated with an increased risk of postoperative recurrence compared to TRG1a. The combined TRG1(a&b) group demonstrated significantly longer recurrence-free survival (RFS) compared to the TRG2 (P = 0.0075) and TRG3 (P < 0.001) groups, respectively. Independent predictors for achieving TRG1(a&b) included male gender (OR = 3.44, P < 0.001), treatment with TACE combined with targeted therapy and immunotherapy (P < 0.001), pre-treatment tumor diameter of 5–10 cm (OR = 2.31, P = 0.012), and rapid normalization of AFP levels (OR = 0.97, P < 0.001).ConclusionsAchieving TRG1 status (0-10% residual tumor) following conversion therapy is associated with significantly improved RFS in patients with intermediate-advanced HCC. Male patients, tumors measuring 5–10 cm, combined TACE with systemic therapies, and rapid normalization of AFP levels are significant predictors for achieving TRG1 status.Clinical Trial RegistrationChiCTR2400088877.